Impacts of universal health coverage: A micro-founded macroeconomic perspective - Xianguo Huang; Naoyuki Yoshino (Asian Development Bank Institute (ADBI), 2015)
This paper studies the impact of tax-financed universal health coverage schemes on macroeconomic aspects of labor supply, asset holding, inequality, and welfare, while taking into account features common to developing economies, such as informal employment and tax avoidance, by constructing a dynamic stochastic general equilibrium model with heterogeneous agents. Agents have different education levels, employment statuses, and idiosyncratic shocks. Given three tax financing options, calibration results suggest that the financing options matter for outcomes both at the aggregate and disaggregate levels. Universal health coverage, financed by labor income tax revenue, could reduce inequality due to its large redistributive role. Social welfare cannot be improved when labor decisions are endogenous and distortions are higher than the redistributive gains for all tax financing options. In the absence of labor supply choice, mild welfare gains are found.
Keywords: E24; E26; E62; J11; H23; H51; 330; universal health coverage; DSGE model; idiosyncratic shocks; social welfare